An examination of firm’s entrepreneurial orientation, innovation and performance of large manufacturing firms in Pakistan - Waris Ali Khan; Ramraini Ali Hassan; Syed Azizi Wafa Syed Khalid Wafa; Muhammad Zulqarnain Arshad; Umair Kashif; Asifa Nisar (Penerbit UMS, 2019)
The purpose of this paper is to extend the understanding of relationships between entrepreneurial orientation, and performance of large manufacturing firms in Pakistan and to examine the role of innovation as a mediator of the above relationship. The paper presents a review of studies containing empirical research incorporating entrepreneurial orientation, innovation and firm performance. On the basis of literature, a model of the relationship of variables has been developed. In total, 320 owners/managers of manufacturing firms in Pakistan completed the survey questionnaire and the data was analyzed using PLS-SEM. The study found a negative relationship between entrepreneurial orientation and performance, however, further reveals that innovation mediates the relationship between entrepreneurial orientation and performance. The major contribution of this paper is to explore the mediating impact of innovation on the relationship between entrepreneurial orientation, and performance of large manufacturing firms in Pakistan. The originality of this paper is that it provides useful implication for different types of organizations to understand the relationship of entrepreneurial orientation, and innovation to introduce innovative products and processes and to improve a firms performance.